2022
DOI: 10.3389/fonc.2022.942798
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid desaturase 1 (FADS1) is a cancer marker for patient survival and a potential novel target for precision cancer treatment

Abstract: Fatty Acid Desaturase-1 (FADS1) or delta 5 desaturase (D5D) is a rate-limiting enzyme involved in the biosynthesis of long-chain polyunsaturated fatty acids (LC-PUFAs), i.e., arachidonic acid (ARA) and eicosapentaenoic (EPA). These LC-PUFAs and their metabolites play essential and broad roles in cancer cell proliferation, metastasis, and tumor microenvironment. However, the role of FADS1 in cancers remains incompletely understood. Utilizing The Cancer Genome Atlas (TCGA) database, we explored the role of FADS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…Other authors showed that ccRCC tissue samples exhibited higher levels of linoleic acid compared to normal renal tissue. , Taking into account the role of this essential fatty acid as a precursor of several long-chain polyunsaturated fatty acids (LC-PUFAs) involved in immunity regulation and inflammatory response, its downregulation after surgery in ccRCC patients with good prognosis may be related to an improved outcome. Moreover, high mRNA expression of fatty acid desaturase-1 (FADS1, a key enzyme involved in the biosynthesis of LC-PUFAs) in tumors, was associated with worse overall survival and disease-free survival, in particular for ccRCC, papRCC, and chRCC patients . Although more studies are needed to unravel the dietary lipid influence in ccRCC, , our results highlight linoleic acid and its metabolism as interesting targets to be monitored during patient follow-up.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Other authors showed that ccRCC tissue samples exhibited higher levels of linoleic acid compared to normal renal tissue. , Taking into account the role of this essential fatty acid as a precursor of several long-chain polyunsaturated fatty acids (LC-PUFAs) involved in immunity regulation and inflammatory response, its downregulation after surgery in ccRCC patients with good prognosis may be related to an improved outcome. Moreover, high mRNA expression of fatty acid desaturase-1 (FADS1, a key enzyme involved in the biosynthesis of LC-PUFAs) in tumors, was associated with worse overall survival and disease-free survival, in particular for ccRCC, papRCC, and chRCC patients . Although more studies are needed to unravel the dietary lipid influence in ccRCC, , our results highlight linoleic acid and its metabolism as interesting targets to be monitored during patient follow-up.…”
Section: Resultsmentioning
confidence: 77%
“…Moreover, high mRNA expression of fatty acid desaturase-1 (FADS1, a key enzyme involved in the biosynthesis of LC-PUFAs) in tumors, was associated with worse overall survival and disease-free survival, in particular for ccRCC, papRCC, and chRCC patients. 61 Although more studies are needed to unravel the dietary lipid influence in ccRCC, 62,63 our results highlight linoleic acid and its metabolism as interesting targets to be monitored during patient follow-up.…”
Section: Metabolic Shift In Post-operative Siv-ccrcc Patientsmentioning
confidence: 79%
“…3A). Fatty Acid Desaturase 1(FADS1) plays a regulatory role in the anabolism of long-chain polyunsaturated fatty acids (44), which was rst cloned in 1999 and was found on the human genome chromosome 11q12-11q13.1. ( 45).…”
Section: Discussionmentioning
confidence: 99%
“…PUFAs and their derivatives have been implicated to play broad functions in cancer impacting various stages from tumorigenesis to progression and metastasis (24)(25)(26)(27)(28). Previous research has shown that Fatty Acid Desaturase 1 (FADS1), a rate-limiting enzyme in LC-PUFA bioproduction, plays a significant role in the growth of various cancer cells (13) and is overexpressed in colon, pancreas, breast, and laryngeal cancers (29). However, whether the LC-PUFA production, controlled by FADS1, plays a similar role as MUFAs remains to be explored.…”
Section: Introductionmentioning
confidence: 99%